The Transportation Problem with Stochastic Demand - Szwarc, Wlodzimierz (Management Science, 1964)
The transportation problem with stochastic demand is considered when penalties are paid for each oversupplied and undersupplied unit of product. The transportation plan minimizing the total transportation costs plus total expected penalty cost of both kinds is to be found. The paper presents a method of solution which is preceded by a development that replaced the original cost function with a controlled linear approximation.